Keabsahan Blockchain-Smart Contract Dalam Transaksi Elektronik: Indonesia, Amerika Dan Singapura - Eureka Inola Kadly; Sinta Dewi Rosadi; Elisatris Gultom (LPPM Universitas Jambi, 2021)
Information technology changes people's habits in simple transactions to electronic systems (e-commerce). Along with technological developments, various new electronic contract innovations have emerged, one of which is the Blockchain-Smart Contract which relies on a decentralized ledger system in digital form that moves automatically (self-executing) using cryptocurrency on the blockchain. With its application in electronic transactions carried out without human intervention and based on computer code, it raises various questions regarding its validity as an electronic contract that is binding and enforceable both in the Law on Information and Electronic Transactions (UU ITE) in Indonesia, as well as internationally in UNCITRAL's Legal Model on e-Commerce with the implementation of technology neutrality principles.